2021
DOI: 10.3390/fermentation8010009
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Yeasts with Probiotic Traits for Kefir Production: Effectiveness of the Microbial Consortium

Abstract: Kefir is a fermented milk made by beneficial lactic acid bacteria and yeasts inoculated as grains or free cultures. In this work, five yeast strains with probiotic aptitudes belonging to Candida zeylanoides, Yarrowia lipolytica, Kluyveromyces lactis, and Debaryomyces hansenii species were assessed in a defined consortium, in co-culture with a commercial strain of Lactobacillus casei, in order to evaluate the yeasts’ fermentation performance during kefir production, using different milks. The concentration of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Due to the lack of reliable population of microorganisms in commercial kefir starter cultures, a remarkable diminution in sensory properties is usually observed. In fact, fermented dairy products develop their unique organoleptic and functional attributes as result from the metabolic activity of the multispecies microflora, where more than one type of interaction may occur concomitantly [ 12 ]. Kefir can also be manufactured from natural kefir starter culture, which is initially captured from kefir grains with the same microbial composition.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of reliable population of microorganisms in commercial kefir starter cultures, a remarkable diminution in sensory properties is usually observed. In fact, fermented dairy products develop their unique organoleptic and functional attributes as result from the metabolic activity of the multispecies microflora, where more than one type of interaction may occur concomitantly [ 12 ]. Kefir can also be manufactured from natural kefir starter culture, which is initially captured from kefir grains with the same microbial composition.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to sensory analysis, it has been reported that the ovine kefir is more appreciated than the goat kefir [31]. The sensory scores of our ovine and goat kefirs showed significant differences but some sensorial aspects of both kefirs can be improved.…”
Section: Discussionmentioning
confidence: 67%
“…Some authors developed synbiotic drinks from milk fermented by kefir grains and supplemented by inulin, quinoa flour, or with the addition of specific probiotic bacteria [20,29,30]. However, most available milk-based kefir products on the market are produced without kefir grains; they use commercial kefir cultures [31]. This study will also aim to develop new synbiotic kefir products based on sheep's and goat's UF concentrated CW, fermented by kefir grains or commercial kefir starter, with and without the addition of a commercial probiotic culture, and supplemented with inulin.…”
Section: Introductionmentioning
confidence: 99%
“…During the fermentation of foods and beverages, like wine, beer and cheese, aromatic chemicals are created in large part as a result of yeast growth. 1,2 Meanwhile, yeast is often used to build cell factories to produce various chemicals or nutrient substances. 3,4 Efficiencies of cell proliferation and product accumulation may be impacted by the stressful environments encountered by cells during fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…During the fermentation of foods and beverages, like wine, beer and cheese, aromatic chemicals are created in large part as a result of yeast growth 1,2 . Meanwhile, yeast is often used to build cell factories to produce various chemicals or nutrient substances 3,4 .…”
Section: Introductionmentioning
confidence: 99%